Prototipe Alat Pendeteksi dan Pengumpul Serpihan Logam Berbasis Remote Control - Irham Fadilah; Endah Fitriani; Rahmat Novrianda Dasmen; Nina Paramytha (TELKA - Telekomunikasi Elektronika Komputasi dan Kontrol, 2026)
Handling metal cutter debris in the tissue processing industry poses a significant risk of physical injury, compromising Occupational Health and Safety (OHS). To address this issue, this research aimed to design, build, and test the functionality of a remote-controlled prototype for detecting and collecting metal fragments. This study applied a Research and Development (R&D) methodology, resulting in a Robot Unit (Receiver) equipped with an SN04-N2 metal proximity sensor, an HC-SR04 ultrasonic sensor, and an electromagnet-based collection mechanism. Operational control was performed via a Control Unit (Transmitter) using the ESP-NOW wireless communication protocol. The test results show that the device characteristics include a stable communication range of up to 220 meters in an outdoor environment. The metal detection limit is effective at a 3 mm distance, with an electromagnetic mechanism capable of lifting a maximum load of 41.2 grams at a lifting distance of 0.3 cm. However, the operational endurance of the Receiver Unit is recorded at 1 hour and 34 minutes. From these results, the conclusion of this study is that the prototype successfully functions as intended, with reliable communication and actuator strength as its main advantages. However, power efficiency and the challenge of precise remote positioning are its primary limitations that require further development.